2013
DOI: 10.1080/17482798.2012.739806
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Internet Mediation:

Abstract: This article empirically examines if parents apply new types of mediation for the internet, using data from the Dutch EU Kids Online project. The high internet penetration in the Netherlands makes this study especially relevant because almost all parents and children use the internet. Factor analyses applied to reports by parents and children (aged 9-16) revealed four mediation types that are comparable for both groups: active safety mediation, restrictive content mediation, restrictive technical mediation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 25 publications
13
76
0
14
Order By: Relevance
“…Instead, the study aims to offer new insights into those aspects of parental mediation that receive little attention in quantitative studies as well as to make suggestions for future research in this field. internet use also engage more in mediation practices (Sonck et al, 2013). It is warranted that future studies would pay more attention to the ways in which parents define their own role regarding their children's internet use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the study aims to offer new insights into those aspects of parental mediation that receive little attention in quantitative studies as well as to make suggestions for future research in this field. internet use also engage more in mediation practices (Sonck et al, 2013). It is warranted that future studies would pay more attention to the ways in which parents define their own role regarding their children's internet use.…”
Section: Discussionmentioning
confidence: 99%
“…give their interpretations of media content and to convey their opinions about it), restrictive mediation (restrictions with regard to the time spent online as well as the media content that a child may consult), supervision and co-use (watching the child using the internet and using the internet with the child regardless of any discussions taking place), interaction restrictions (rules about with whom the child can communicate) and technological mediation (the installation of technical applications that enable parents to track their children's online activities or to limit their internet access) (Livingstone & Helsper, 2008;Sonck et al, 2013; M A N U S C R I P T…”
Section: Literature Review Parenting the Internet 20: Strategies Andmentioning
confidence: 99%
“…Active mediation refers to parents discussing the risks related to internet use and teaching their children how to avoid online risks. Restrictive mediation refers to all sorts of practices that restrict or track the child's internet use, e.g., setting rules about when or where the child can be online, who the child can talk to or which websites the child can visit, supervising the child's internet behavior and making use of blocking or monitoring software (e.g., Livingstone and Helsper 2008;Sonck et al 2013;Valkenburg et al 2013).…”
Section: Sources Of Parental Knowledgementioning
confidence: 99%
“…The literature suggests that parents tend to report more monitoring and knowledge-related behaviors than adolescents but that adolescents' reports are more strongly related to behavioral outcomes than their parents' reports (Abar et al 2015). Also, with regard to internet use, parents are found to report more monitoring practices such as rule-setting, technical mediation, safety communication and supervision (Liau et al 2008;Wang et al 2005;Sonck et al 2013) than adolescents. Future research could take into account the relevance of parent-child discrepancies in reports on monitoring practices in terms of parental knowledge.…”
Section: Limitationsmentioning
confidence: 99%
“…On the individual level, studies have indicated that parental mediation can be related to demographic variables, such as the age and gender of the parents (Kirwil, Garmendia, Garitaonandia, & Martínez Fernández, 2009;Sonck, Nikken, & de Haan, 2013); the parents' education ; the age and gender of the children (Eastin, Greenberg, & Hofschire, 2006;Livingstone & Helsper, 2008); the household socioeconomic status (Livingstone & Helsper, 2008); and the family size (Sonck et al, 2013). Parental mediation is also associated with the parents' perceptions of their children's digital skills (Livingstone, Ólafsson, et al, 2017); the level of the child's (Lee & Chae, 2012) and the parents' media literacy (Mendoza, 2009); the level of the parents' digital skills (Livingstone & Helsper, 2008); the child's motivation to use media; the frequency of media use in the family (Lee & Chae 2007;Livingstone & Helsper, 2008); and the parents' views on the various effects of media content on their children (Sonck et al, 2013). On the socio-cultural level, studies have indicated that parental mediation of their children's internet use is affected by the culture of their country (i.e., countries' individualistic or collectivistic values; Kirwil, 2009) and their country's level of welfare (Kalmus & Roosalu, 2012).…”
Section: Factors Associated With Parental Mediationmentioning
confidence: 99%